Determinant of auditor’s ability to detect fraud - Rosida Maedina Agus; Arifuddin; Asri Usman; Sri Sundari (IECON: International Economics and Business Conference, 2024)
This study investigates the role of auditors in carrying out responsibilities, because it is very important to support their performance. Auditors are expected to be able to detect fraud in financial reports so that no party is harmed. This research aims to analyze the effect of Self Efficacy, Professional Skepticism, Emotional Intelligence on fraud detection.  The research method uses descriptive quantitative, data analysis uses SEM PLS. The data collection method in this research uses a questionnaire method. Next, a questionnaire will be created using Google Form.  The Google form link to the questionnaire will be sent officially to the representative BPK auditor in South Sulawesi. The research results show that self-efficacy has a significant effect on fraud detection. Professional skepticism has a significant effect on fraud detection. Emotional intelligence has a significant effect on fraud detection. Furthermore, Information Technology is able to moderate Self Efficacy, Professional Skepticism, Emotional Intelligence in fraud detection.  The findings show that an auditor in carrying out his responsibilities needs to understand an auditor's attitude in detecting fraud because it is very important to support his performance. Auditors are expected to be able to detect and eliminate fraud in financial reports so that no party is harmed. To carry out the auditor's function, good intelligence is needed in order to achieve more optimal performance. Rational and analytical thinking processes as well as self-efficacy skills, professional skepticism, emotional intelligence, and information technology are very important for auditors because they are very helpful in detecting fraud. So in this research the broad theories used are attribution theory and the Theory of Planned Behavior (TPB) which explains intentions, attitudes and behavior that influence a person's actions.